Situation analysis - Denault, Jean-François (Henry Stewart Talks, 2020)
Internal analysis, External analysis, SWOT (strengths, weaknesses, opportunities, threats), TOW (opportunities, weaknesses and strengths), Competitive analysis, Customer analysis